2013
DOI: 10.1111/afe.12005
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring oak processionary moth Thaumetopoea processionea L. using pheromone traps: the influence of pheromone lure source, trap design and height above the ground on capture rates

Abstract: 1 A field trial conducted in the summer of 2011 evaluated three key parameters that might be influential for determining the number of adult male oak processionary moths (OPM) Thaumetopoea processionea (L.) caught in pheromone traps. Two types of traps (Delta and funnel; Oecos, U.K.) containing one of three different commercially available pheromone lures for OPM were placed out in the lower (3-5 m), mid (5-10 m) and upper (10-15 m) canopy of 72 individual oak trees in Richmond Park, in London, U.K. 2 The trap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 37 publications
0
20
0
1
Order By: Relevance
“…The OPM pheromone lures were obtained from Pherobank (The Netherlands) and the pheromone traps used were the standard green funnel traps supplied by Oecos (Kimpton, U.K.). All traps were positioned in the tree canopy between approximately 10 and 16 m from the ground because previous studies have demonstrated that, at this height, there is a greater efficiency at catching male OPM in pheromone traps (Breuer et al ., ; Williams et al ., ). The positioning of traps at this height in the canopy was achieved using a set of carbon‐fibre telescopic poles (Telsys Ltd, U.K.), which enabled a weight attached to a polyethylene throw‐line to be dropped over a suitable branch in the tree canopy.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…The OPM pheromone lures were obtained from Pherobank (The Netherlands) and the pheromone traps used were the standard green funnel traps supplied by Oecos (Kimpton, U.K.). All traps were positioned in the tree canopy between approximately 10 and 16 m from the ground because previous studies have demonstrated that, at this height, there is a greater efficiency at catching male OPM in pheromone traps (Breuer et al ., ; Williams et al ., ). The positioning of traps at this height in the canopy was achieved using a set of carbon‐fibre telescopic poles (Telsys Ltd, U.K.), which enabled a weight attached to a polyethylene throw‐line to be dropped over a suitable branch in the tree canopy.…”
Section: Methodsmentioning
confidence: 97%
“…The moth was accidentally introduced into the U.K. via the importation of infested oak trees, and since the discovery of larvae in 2006 in west London it has slowly spread over a wider area despite eradication and subsequent containment efforts (Townsend, & ; Cowley et al ., ). Monitoring the spread of OPM has been an integral part of the attempts to manage and control this invasive insect pest, and hence the development and use of an effective pheromone trapping system has been essential (Straw et al ., ; Williams et al ., ). For rapid action, it is vitally important to ensure that an efficient monitoring system is utilized to inform landowners as early as possible that OPM has reached previously uninfested trees in woodlands, parks and other amenity areas.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…We baited each trap with one different pheromone lure, obtained from Temmen GmbH Biotechnologie (Germany) (lure 1) and Pherobank (The Netherlands) (lure 2). Each trap was positioned in the upper canopy (10-15 m) to maximize captures (Breuer et al, 2003;Williams et al, 2013). The traps were active from late June to late August 2018, corresponding to the expected flight period of the OPM in France.…”
Section: Effect Of Forest Stand Composition On Opm Moth Capturesmentioning
confidence: 99%
“…They are an integral part of the food chain of insectivorous birds (Krištín and Patočka 1997;Buse et al 1999;Visser et al 2006), mice (Elkinton et al 1996) and bats (Vaughan 1997), provide pollination services (Pettersson 1991;Devoto et al 2011), and have economic importance as pests in agriculture (Calkins 1998;Furlong et al 2013), forestry (Benigni and Battisti 1999;Williams et al 2013) and warehouses (Ryne et al 2006;Rondon 2010;Campos and Phillips 2014). In recent decades, they have been seen as useful indicators of environmental quality (Thomas 2005).…”
Section: Introductionmentioning
confidence: 99%